The Role of Ocean Heat Transport in Rapid Sea Ice Declines in the Community Earth System Model Large Ensemble. Issue 12 (10th December 2018) - Auclair, Gabriel; Tremblay, L. Bruno
Abstract: Many climate models, including the Community Earth System Model Large Ensemble (CESM‐LE), predict future rapid sea ice declines in the Arctic linked with anomalies in northward Ocean Heat Transport (OHT). Using CESM‐LE, we find that the partitioning of the poleward OHT between the different Arctic gates (Barents Sea Opening, BSO; Bering Strait; and Fram Strait) is key to this link with the rapid declines. Sixty‐four of the 79 rapid declines in CESM‐LE are correlated with the OHT anomalies through one of the gates. Rapid declines that happen earlier in the simulations when the sea ice covers the continental shelves are correlated with OHT anomalies. The interaction between OHT and sea ice happens mainly over continental shelves since most rapid declines are correlated with the BSO or Bering Strait OHTs and only a few with the Fram Strait OHT (often also correlated with BSO or Bering Strait OHTs). In most rapid declines not correlated with OHT, the September Sea Ice Extent (SIE) prior to the decline is smaller than the area covered by the deep basins. Those are associated with surface heat flux since the ice‐atmosphere heat fluxes are more strongly correlated with the sea ice concentrations over the deep basins than the ice‐ocean heat fluxes. Our results suggest that OHTs are causing rapid sea ice declines when the SIE is large enough to cover the continental shelves and that the atmosphere is the main driver when the initial SIE is located only over the deep basins. Plain Language Summary: A significant decrease in the minimum sea ice extent has been observed since the beginning of the satellite era in the late seventies. Several climate models simulate drastically different future evolution of the minimum sea ice extent. In this study, we use output diagnostics from the Community Earth System Model Large Ensemble to verify if the pathway of ocean heat transport entering the Arctic has an impact on the presence or absence of rapid sea ice declines. We find that the interaction between ocean heat transport and sea ice happens mainly over the shallow continental shelves. There, ocean heat transport can contribute to the melting of the sea ice. This melting is afterward enhance by positive feedbacks, such as the ice‐albedo feedback, and can lead to a rapid decline of the Arctic sea ice cover. In the central Arctic, the sea ice is more sensitive to atmospheric heat than to ocean heat. Key Points: Rapid sea ice declines in the Arctic are correlated with anomalies in ocean heat transport The partitioning of the ocean heat transport between the different Arctic gates is a key factor to this link and to the geographical location of the declines The interaction between the ocean heat transports and the sea ice happens mainly on the shallow continental shelves